Identification of Epigallocatechin-3- Gallate as an Inhibitor of Phosphoglycerate Mutase 1 - Li, Xiaoguang; Tang, Shuai; Wang, Qian-Qian; Leung, Elaine L.-H.; Jin, Hongyue; Huang, Yongzhuo; Liu, Jia; Geng, Meiyu; Huang, Min; Yuan, Shengtao; Yao, Xiao-Jun; Ding, Jian (Frontiers in Pharmacology, 2017)
Targeting metabolic enzymes is believed to provide new therapeutic opportunities for cancer therapy. Phosphoglycerate mutase 1 (PGAM1) is a glycolytic enzyme that importantly coordinates glycolysis, pentose phosphate pathway (PPP) flux and serine biosynthesis in cancer cells and hence gains increasing interest of inhibitor discovery. Only few PGAM1 inhibitors have been reported and the molecular potency remains very limited. In an effort to discover new PGAM1 inhibitors, we carried out a biochemical assay-based screen that was focused on natural products derived small molecule compounds. (-)-Epigallocatechin-3-gallate (EGCG), the major natural catechins of green tea extract, was identified as a PGAM1 inhibitor that was tremendously more potent than known PGAM1 inhibitors. Further studies combining molecular docking and site-specific mutagenesis revealed that EGCG inhibited PGAM1 enzymatic activity in a manner independent of substrate competition. EGCG modulated the intracellular level of 2-phosphoglycerate, impaired glycolysis and PPP and inhibited proliferation of cancer cells. This study suggested EGCG as a chemical scaffold for the discovery of potent PGAM1 inhibitors and gained mechanistic insights to understand the previously appreciated anticancer properties of EGCG.